CONCEPTUAL PROJECTS OF OLEKSANDR SUKHOLIT IN THE CONTEXT OF THE DEVELOPMENT OF UKRAINIAN ART IN THE 1990s - Цигикало, К. О. (Art and Design, 2022)
Purpose: to find out the features of Oleksandr Sukholit's art in the context of the development of Ukrainian art in the 1990s; to describe the main ideas of the sculptural workshop "Azbuka" (1992) and the project "Hierarchy of Space" (1992), to determine the place of personality in the art of this period. Methodology. In the process of research, the following methods were used: art history analysis, analysis of the theoretical prerequisites for the development of plastic ideas with the analysis of specific works; synthesis, generalization and systematization of the received information; biographical method; methods of induction, deduction and comparative analysis. Results. In the 1990s, a representative of the Kyiv school of sculpture, a graduate of the Kyiv State Art Institute (now National Academy of Fine Art and Architecture), projects that today are considered as an important phenomenon and are called a significant point in the art of sculpture of the last decade of the 20th century. The article describes the history of the founding of seminary practices, indicates the ideas followed by the artists, the purpose of their work. The basic principles of the work of the seminar "Azbuka" were determined, where worked O. Sukholit, A. Polonik, O. Ridny, R. Kukhar also participated. In the article is presented detailed description of the exposition of the exhibition of the seminar "Hierarchy of Space", comments of eyewitnesses, reviews of artists, as well as art critics reviews are given. Attention is paid to the ideas of the sculptor regarding the philosophy of space and its significance for sculpture: rhythm, line, light, alternation of objects in the space of the exhibition hall. The scientific novelty of the study lies in the identification of searches and experiments, the characteristic features of conceptualism in the works of Oleksandr Sukholit in the context of the development of Ukrainian art of the last decade, in the introduction of the sculptural workshop "Azbuka" (1992) and the project "Hierarchy of Space" (1992) into the context of a special art criticism study. Practical significance. The features of the creative method of the artist O. Sukholit in the period of 1980-1990s are determined. The study is an important link in the further study of the history of Ukrainian sculpture.